Weighted gene co-expression network analysis reveals key module and hub genes associated with the anthocyanin biosynthesis in maize pericarp - Li, Tingchun; Wang, Yiting; Dong, Qing; Wang, Fang; Kong, Fanna; Liu, Guihu; Lei, Yanli; Yang, Huaying; Zhou, Yingbing; Li, Cheng (Frontiers in Plant Science, 2022)
Anthocyanins are the visual pigments that present most of the colors in plants. Its biosynthesis requires the coordinated expression of structural genes and regulatory genes. Pericarps are the rich sources of anthocyanins in maize seeds. In the experiment, the transcriptomes of transparent and anthocyanins-enriched pericarps at 15, 20, and 25 DAP were obtained. The results output 110.007 million raw reads and 51407 genes’ expression matrix. Using data filtration in R language, 2057 genes were eventually identified for weighted gene co-expression network analysis. The results showed that 2057 genes were classified into ten modules. The cyan module containing 183 genes was confirmed to be the key module with the highest correlation value of 0.98 to the anthocyanins trait. Among 183 genes, seven structural genes were mapped the flavonoid biosynthesis pathway, and a transcription factor Lc gene was annotated as an anthocyanin regulatory gene. Cluster heatmap and gene network analysis further demonstrated that Naringenin, 2-oxoglutarate 3-dioxygenase (Zm00001d001960), Dihydroflavonol 4-reductase (Zm00001d044122), Leucoanthocyanidin dioxygenase (Zm00001d014914), anthocyanin regulatory Lc gene (Zm00001d026147), and Chalcone synthase C2 (Zm00001d052673) participated in the anthocyanins biosynthesis. And the transcription factor anthocyanin regulatory Lc gene Zm00001d026147 may act on the genes Chalcone synthase C2 (Zm00001d052673) and Dihydroflavonol 4-reductase (Zm00001d044122). The yeast one-hybrid assays confirmed that the Lc protein could combine with the promoter region of C2 and directly regulate the anthocyanin biosynthesis in the pericarp. These results may provide a new sight to uncover the module and hub genes related to anthocyanins biosynthesis in plants.